Facile fabrication of Nd2O2S/C nanocomposite with enhanced microwave absorption induced by defects. Issue 3 (25th November 2021) - Shen, Zhongjing; Peng, Hualong; Xiong, Zhiqiang; Yang, Huili; Huang, Zihao; Huang, Shuyi; Liu, Chongbo
Abstract: The derivatives of metal‐organic frameworks (MOFs) in which various metal and/or metal oxides are uniformly distributed in porous carbon materials have attracted considerable attention owing to their special characteristics such as large specific surface area, adjustable pore structure, highly ordered pores, and uniform metal sites. Presently, the electromagnetic absorption property of MOF derivatives is primarily enhanced by changing their metal ions, and it is still a challenge to improve the loss ability of MOF‐derived absorbers by modifying the organic ligands of MOFs. In this work, rhombic Nd2 O2 S/C nanocomposites with excellent microwave absorption (MA) performance are synthesized via in‐situ pyrolysis of (Nd[TDA][CH3 COO][H2 O])n (H2 TDA: 2, 5‐thiophenedioic acid). The influence of pyrolysis temperature on the MA performance of the composites is examined. The Nd2 O2 S/C‐800 composite exhibits a minimum reflection loss of –52.3 dB at 2.56 mm thickness, which is ascribed to the synergistic effect of multiple loss mechanisms, including polarization, conduction loss, and so forth. Overall, this paper provides a useful method to synthesize high‐performance MA materials by utilizing MOFs with rare‐earth ions connected by sulfur‐containing organic ligand.